Exploiting item relationships for effective recommendation - Sun, Zhu (2018)
To alleviate the data sparsity and cold start issues in recommendation, many researchers leverage user relationships (e.g. social network) to improve the accuracy of recommender systems. However, social connections may not be available in many real systems, whereas item relationships are much easier to obtain but lack of study. Therefore, in this disser- tation, we focus on exploiting item relationships for effective recommendation.